2014
DOI: 10.1021/es404458j
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Water Footprints of Nonfood Biomass Fuels in China

Abstract: This study presented life cycle water footprints (WFs) of biofuels from biomass in China based on the resource distribution, climate conditions, soil conditions and crop growing characteristics. Life cycle WFs including blue, green and gray water were evaluated for the selected fuel pathways. Geographical differences of water requirements were revealed to be different by locations. The results indicated that water irrigation requirements were significantly different from crop to crop, ranging from 2-293, 78-13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…The life-cycle WFs of Jatropha oil in Mozambique are reported to be as high as 15,264 L of water per L of Jatropha oil [46]. In China, the WFs of Jatropha -based biodiesel are estimated to be relatively low [40]. Generally, the water footprints of each biofuel show significant regional differences.…”
Section: Introductionmentioning
confidence: 99%
“…The life-cycle WFs of Jatropha oil in Mozambique are reported to be as high as 15,264 L of water per L of Jatropha oil [46]. In China, the WFs of Jatropha -based biodiesel are estimated to be relatively low [40]. Generally, the water footprints of each biofuel show significant regional differences.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, sustainability and economic feasibility studies of bioethanol production have mainly focused on a specific region or a single aspect of the bioethanol production process [33,35,[66][67][68][69][70][71][72][73]. In addition, comprehensive assessment of sustainability and economic feasibility of sweet sorghum for bioethanol have been insufficient, even among various diverse areas across China.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, great differences in economic output were observed between Wuyuan County and Gulang County in GX, mostly because the sweet sorghum variety in Gulang County is late-maturing and no-heading and has a higher stalk biomass; thus, stalk from Gulang County commands a higher price (57 USD/t) than from Wuyuan County (33 USD/t). Previous sweet sorghum life cycle assessment studies revealed that the GHGs were produced at their highest levels during the planting stage, as a result of N-fertilizer production and application, as well as the use of diesel fuel for farm machinery during this stage [22,71]. Other research [76] reported that in the North China Plain, using diversified crop rotation planting, the production of N fertilizer made the largest contribution to GHG emissions among all agricultural inputs, accounting for an average of 45% of emissions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many researchers have used the WF to evaluate water use in agricultural production (Bocchiola et al, 2013;Chapagain and Hoekstra, 2011;Chapagain and Orr, 2009;Gheewala et al, 2014;Jefferies et al, 2012;Lamastra et al, 2014;Mekonnen and Hoekstra, 2010;Shrestha et al, 2013;Y. B. Wang et al, 2014;Xu et al, 2014;Zang et al, 2014;Suttayakul et al, 2016). The WF of crops reflects the water consumption of different crops, and can focus on local crop products.…”
Section: Introductionmentioning
confidence: 99%